The Effect of Deposition Potential on the Electrodeposition of Platinum Nanoparticles for Ethanol Electrooxidation - Amelia Sabella; Reyhan Syifa; Nandita Annisa Dwiyana (Pusat Inovasi Sains, 2022)
Platinum (Pt) nanoparticles were successfully prepared using square wave pulse deposition technique by varying the upper potential. The X-ray energy dispersive spectrum pattern confirmed the formation of Pt nanoparticles on the fluorine-doped tin oxide coated glass substrate. The results of scanning electron microscopy showed that the potential of 0.60 V was able to produced a large number of Pt particles with a unique morphology. The ethanol electrooxidation test conducted using cyclic voltammetry showed that Pt0.60v has the lowest charge transfer resistance value showing high catalytic activity which could be associated to the increase of particle number and its active sites that activated the redox reactions in the system.